2017
DOI: 10.3390/ijerph14101263
|View full text |Cite
|
Sign up to set email alerts
|

Petroleum Hydrocarbon Profiles of Water and Sediment of Algoa Bay, Eastern Cape, South Africa

Abstract: Petroleum hydrocarbon profiles of water and sediment samples of Algoa Bay in the Eastern Cape Province of South Africa were assessed using standard analytical procedures. Water (from surface and bottom levels) and sediment samples were collected from five locations in the bay from February to June 2016. Extraction of the petroleum hydrocarbons from the water and sediment samples collected was achieved using liquid-liquid and Soxhlet extraction techniques, respectively, followed by column clean up. Target compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 50 publications
8
28
0
Order By: Relevance
“…3). This was in agreement with the reports published earlier, in which the concentrations were also lower in winter (Klages and Bornman 2003; Adeniji et al 2017).
Fig.
…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…3). This was in agreement with the reports published earlier, in which the concentrations were also lower in winter (Klages and Bornman 2003; Adeniji et al 2017).
Fig.
…”
Section: Resultssupporting
confidence: 94%
“…The levels recorded at stations A1 and A2 were relatively the same. The organic carbon contents of the sediment samples from Algoa Bay ranged from 1.06 to 2.05% as documented earlier by Adeniji et al (2017). The values were very consistent with previous report by Klages and Bornman (2005).…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…Massoud et al (1996) and Ritchie et al (2001) Based on this, the sediment samples collected from the 12 sampling sites in the four stations can be regarded as unpolluted in terms of TPH. Adeniji et al (2017) in a study of Algoa Bay, South Africa observed that pH concentrations in the sediment samples ranged from 0.72 to 27.03 mg/kg (dry weight basis) while Inyang et al (2018) obtained TPH concentration range of 270-830 mg/kg in the sediment samples of Qua-Iboe River, Akwa-Ibom State. These values were much higher than the TPH values obtained in this study.…”
mentioning
confidence: 98%